The regulation of artificial intelligence: he complexity in the search for a balance of interests. Special focus on the protection of creation and innovation. Comparative view EU-Colombia - Jiménez Serranía, Vanessa; Calderón Marenco, Eduardo Andrés; Agón López, Juan Guillermo; Ravelo Franco, Gabriel (DIXI, 2025)
The article examines the legal and ethical challenges associated with the integration of artificial intelligence (AI) into the regulatory frameworks of Colombia and the European Union, addressing the tension between technological innovation and the protection of fundamental rights such as privacy and intellectual property. Using a qualitative methodology based on a comparative analysis of regulations, ethical principles, and relevant case law, the study identifies regulatory gaps in Colombia, including the lack of clear guidelines on the ownership of rights in AI-generated creations and the absence of transparency in automated decision-making processes.The findings highlight how the European Union leads with its AI Regulation, establishing clear principles of safety, accountability, and non-discrimination, offering a robust model to balance public and private interests. In contrast, Colombia faces significant challenges in adapting its regulations to current technological complexities.The article concludes by proposing a hybrid approach that combines international standards with local particularities, strengthening technological governance and international cooperation to ensure inclusive, ethical, and sustainable development in the digital era.
Keywords: Technological governance; ntellectual property; Algorithmic transparency; Innovation; Comparative regulation